Tax Literacy: Basic Tax Education for MSMEs in Cipayung District, East Jakarta - Darmastuti, Dewi; Wibawaningsih, Ekawati Jati; Surbakti, Lidya Primta (⁠International Journal of Asia Pacific Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia often face tax compliance. This problem is also experienced by MSME actors in Cipayung District, East Jakarta. A challenge addressed through a Community Service initiative aimed at strengthening foundational tax literacy. The program sought to enhance participants’ understanding of tax regulations, improve documentation accuracy, mitigate penalty risks, and promote business resilience. Conducted by accounting faculty and graduate students from Universitas Pembangunan Nasional "Veteran" Jakarta, the initiative featured workshops on updated tax policies, supplemented by feedback collection via digital surveys. Participants also can consult on tax issues that they experience in their business practices. Results revealed that all participants were satisfied, with acknowledgment of the program’s practical value and requests for follow-up training. This activity highlights the critical role of continuous tax education in fostering sustainable MSME development and compliance.